Petroleum reservoir rock and fluid properties - Dandekar, Abhijit Y. (Boca Raton, FL : CRC Press, 2013)
"The primary purpose and scope of this book was already covered in great details in the 1st edition. Therefore, rather than repeating that information again and dwelling on the details, only the highlights and changes made in the 2nd edition distinguishing it from the 1st edition are included here. Chapter 1 still serves as an overall introduction to petroleum reservoir rock and fluid properties, but has now been organized in a more systematic and easy to understand manner. The discussion begins with a basic definition and significance of "petroleum"; "reservoir"; "rock" and "fluids"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Petroleum -- Fluid dynamics; Petroleum -- Mechanical properties; Petroleum engineering; Petroleum reserves; Oil reservoir engineering